SISI LAIN PENDIDIKAN ISLAM - Nur Hamzah (AT-TURATS, 2014)
In Indonesian education system, the madrasah is one of the most important institutions. This is because of the madrasah serves as the bridge connecting the purely religious education --such as the boarding school, mosque and surau-- and modern public education such as schools. Regarding the aspect of scientific development, the madrasah develops and teaches sciences commonly taught in the public school as well as teaching religious education normally instructed in the boarding school. In the domain of teaching method and system, the madrasah education is also an innovation and development of the methods implemented in the boarding school. Therefore, the madrasah an education institution that teaches both general and religious-based sciences. However, some madrasahs are facing complicated issues such as the problem of human resources, facilities, sources of funds, incompetent management, government policies that are not in favor of the madrasah, and the graduates that are not prepared to compete in the global era.